2013
DOI: 10.5194/tc-7-583-2013
|View full text |Cite
|
Sign up to set email alerts
|

An updated and quality controlled surface mass balance dataset for Antarctica

Abstract: Abstract. We present an updated and quality controlled surface mass balance (SMB) database for the Antarctic ice sheet. Importantly, the database includes formatted metadata, such as measurement technique, elevation, time covered, etc, which allows any user to filter out the data. Here, we discard data with limited spatial and temporal representativeness, too small measurement accuracy, or lack of quality control. Applied to the database, this filtering process gives four times more reliable data than when app… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
106
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(111 citation statements)
references
References 34 publications
5
106
0
Order By: Relevance
“…10, Hg tot concentrations increased between 600-800 and 1000-1100 km from DC in areas characterized by steeper slopes and higher snow accumulation values. Several studies reported a gradual increase in snow accumulation from DC toward the coast (Magand et al, 2007;Verfaillie et al, 2012;Favier et al, 2013), in good agreement with a gradual increase in humidity (Bromwich et al, 2004). These results suggest that the wet deposition of Hg(II) species was enhanced near the coast, resulting in elevated Hg tot concentrations in surface snow samples.…”
Section: Transect From Central To Coastal Antarcticasupporting
confidence: 66%
“…10, Hg tot concentrations increased between 600-800 and 1000-1100 km from DC in areas characterized by steeper slopes and higher snow accumulation values. Several studies reported a gradual increase in snow accumulation from DC toward the coast (Magand et al, 2007;Verfaillie et al, 2012;Favier et al, 2013), in good agreement with a gradual increase in humidity (Bromwich et al, 2004). These results suggest that the wet deposition of Hg(II) species was enhanced near the coast, resulting in elevated Hg tot concentrations in surface snow samples.…”
Section: Transect From Central To Coastal Antarcticasupporting
confidence: 66%
“…Ice core data used in this study. Data citations can be found in Table S1 and in Thomas (2017 Philippe et al (2016) building upon previous SMB compilation studies by Favier et al (2013) and Frezzotti et al (2013). Of the 79 records selected, 41 records extend over the past 200 years, and therefore this period has been selected as a focus for our reconstruction.…”
Section: Antarctica 2k Snow Accumulation Databasementioning
confidence: 99%
“…Mass losses from meltwater runoff are small in Antarctica, except for some parts of the Antarctic Peninsula. Multiple in situ SMB observations can be combined to produce an SMB map for selected ice sheet regions (Rotschky et al, 2007) or for the entire AIS (Favier et al, 2013). Alternatively, SMB can be simulated by (regional) atmospheric climate models, such as the Regional Atmospheric Climate Model (RACMO) version 2.3 (Van Wessem et al, 2014), and various reanalysis products such as ERA-Interim (Dee et al, 2001) or JRA55 (Kobayashi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…ice cores, stake arrays and bomb horizons ( Fig. 1) (Turner et al, 2002;Favier et al, 2013;Scambos et al, 2014). Included in these data are five unpublished in situ observations from high elevations, obtained from a shallow ice core, sonic snow height measurements and camera observations of a snow stake over time (T. A.…”
Section: In Situ Observationsmentioning
confidence: 99%
“…Measuring AP SMB is a complicated task, as the high precipitation rates and the steep mountainous (and inaccessible) terrain leave large regions devoid of observational data; most observations are therefore located in relatively dry areas and/or over the flat ice shelves which are easily accessible (Favier et al, 2013). Ice and firn core observations have identified a doubling of accumulation over the WAP since 1850 (Thomas et al, 2008), an increase in AP SMB over the last 50 years (Peel, 1992), and a large spatial variability of the SMB (Turner et al, 2002).…”
Section: Introductionmentioning
confidence: 99%